2013
DOI: 10.1002/jcph.153
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of ceftaroline in patients with acute bacterial skin and skin structure infections or community‐acquired bacterial pneumonia

Abstract: Ceftaroline, the active form of ceftaroline fosamil, is a broad-spectrum cephalosporin antibiotic. A population pharmacokinetic (PPK) model for ceftaroline was developed in NONMEM® using data from 185 healthy subjects and 92 patients with acute bacterial skin and skin structure infection (ABSSSI). Data from 128 patients with community-acquired bacterial pneumonia (CABP) were used for external model validation. Healthy subjects received 50-2,000 mg ceftaroline fosamil via intravenous (IV) infusion over 1 hour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 19 publications
4
42
0
Order By: Relevance
“…Similar power relationships between body size descriptors and the volume of distribution of ceftaroline (TBW with ␤ ϭ 0.46; BSA with ␤ ϭ 1.35) have been reported in previous POP-PK analyses based on earlier clinical trial data sets (27,31). The inclusion of this covariate in the present model is likely due to the wide, stratified distribution of body size descriptors in our study.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Similar power relationships between body size descriptors and the volume of distribution of ceftaroline (TBW with ␤ ϭ 0.46; BSA with ␤ ϭ 1.35) have been reported in previous POP-PK analyses based on earlier clinical trial data sets (27,31). The inclusion of this covariate in the present model is likely due to the wide, stratified distribution of body size descriptors in our study.…”
Section: Discussionsupporting
confidence: 76%
“…First, the study here enrolled healthy subjects who typically exhibit decreased pharmacokinetic variability and lower CL T levels compared to infected patients. Previous POP-PK models suggest that subjects in ceftaroline phase 2/3 studies had a 35% higher mean CL T than those in phase 1 studies (27)(28)(29)(30). Given this background, obese class III adults who are acutely infected may theoretically have a higher CL T than that predicted by our model.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In addition, in vitro studies demonstrated that ceftaroline does not inhibit or induce major CYP450 isoenzymes. Population pharmacokinetic analysis did not identify any clinically relevant differences in ceftaroline exposure in patients with ABSSSI or CABP who were taking concomitant medications that are known inhibitors, inducers, or substrates of the cytochrome P450 system; anionic or cationic drugs known to undergo active renal secretion; and vasodilator or vasoconstrictor drugs that may alter renal blood flow (5). Thus, the overall drug-drug interaction potential for ceftaroline can be considered to be low.…”
mentioning
confidence: 98%